2002
DOI: 10.4049/jimmunol.169.4.1669
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Electroporation of Human Monocytes, Followed by Rapid In Vitro Differentiation, Leads to Highly Stimulatory Antigen-Loaded Mature Dendritic Cells

Abstract: Dendritic cells (DC) are professional Ag-capturing and -presenting cells of the immune system. Because of their exceptional capability of activating tumor-specific T cells, cancer vaccination research is now shifting toward the formulation of a clinical human DC vaccine. We developed a short term and serum-free culture protocol for rapid generation of fully mature, viable, and highly stimulatory CD83+ DC. Human monocytes were cultured for 24 h in serum-free AIM-V medium, followed by 24-h maturation by polyribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…In our animal model the incubation of DCs with CpG oligonucleotides had no effect on the uptake and presentation of KLH to autologous T cells. Finally, maturation of DCs was tried using poly(I:C), which was reported to induce maturation in human DCs (21). We observed decreased uptake and presentation of KLH by poly(I:C)-treated DCs, resulting in decreased stimulation of autologous T cells.…”
Section: Generation Of Canine Dcs From Linmentioning
confidence: 88%
“…In our animal model the incubation of DCs with CpG oligonucleotides had no effect on the uptake and presentation of KLH to autologous T cells. Finally, maturation of DCs was tried using poly(I:C), which was reported to induce maturation in human DCs (21). We observed decreased uptake and presentation of KLH by poly(I:C)-treated DCs, resulting in decreased stimulation of autologous T cells.…”
Section: Generation Of Canine Dcs From Linmentioning
confidence: 88%
“…We found that DCs activated by poly(I:C 12 U) electroporation yielded higher numbers of IFN-g-producing cells com- À melanoma cell line 938-mel were lysed. As previous studies have shown that human monocyte-derived DCs passively pulsed with poly(I:C) induce stimulation of antigen-specific CD8 + T cells, 21 we also investigated the capacity of Melan-A-A2 peptideloaded DCs activated by passive pulsing with poly (I:C 12 U) to activate naïve CD8 + T cells. Expansion of antigen-specific CD8 + T cells in vitro was quantified by tetramer analysis, 7 days after the third stimulation.…”
Section: Electroporation With Poly(i:c 12 U) Induces Dendritic Cell Mmentioning
confidence: 99%
“…Recently, we (47,48,61) and others (9,15,22,28,40,54,57) have shown that transfection with mRNA is more effective than mRNA lipofection, peptide pulsing, or viral transduction to generate primary (65) and memory (57) responses. Furthermore, we demonstrated that DC from treatment-naïve HIV-1-seropositive subjects can efficiently be transfected with HIV gag and env mRNA, derived either from consensus subtype B or autologous viral or proviral HIV, and that these DC readily trigger autologous CD4 ϩ and CD8 ϩ T cells to release IFN-␥ and IL-2 in a short-term ex vivo enzyme-linked immunospot (ELISPOT) assay (60).…”
mentioning
confidence: 99%